An experiment to reduce the noise output of the four-hole high-speed handpiece by modifying the control box - Roa, Alberto Antonio C.
To reduce the noise produced by a four-hole high-speed handpiece, an old SS White control box was modified by attaching to it a vacuump pump to suction air out of the handpiece through the exhaust tubing. The noise level of the six handpieces used were measured with a sound level meter with and without the vacuum pump. The results showed that all handpieces ran a average of two decibels quieter with the modified control box which was named the "turbo box".
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.